TEACHER TALK IN ENGLISH CLASSROOM INTERACTION USING SINCLAIR AND COULTHARD MODEL - Friska Octavia; Zainuddin (Universitas Negeri Medan, 2018)
This study deals with teacher talk in English classroom interaction. The objectives of the study were: (a) to find out the types of moves found in the teacher talk used in English classroom interaction based on Sinclair and Coulthard model, and (b) to describe how the types of moves are realized in the teacher talk used in English classroom interaction based in Sinclair and Coulthard model. The design used in this study was qualitative research. The data of this study was the teacher’s utterances. The data was collected by using audio recording and video recording. The data analysis of this study were based on Sinclair and Coulthard model as the following: (a) to find out the types of moves found in the teacher talk, and (b) to describe how the types of moves are realized in the teacher talk used in English classroom interaction. Based on the analysis of the data, the findings were shown as the following: (a) there were four types of moves found in the teacher talk, namely: opening, follow-up, framing and focusing, (b) the types of moves found in the teacher talk were mostly realized by h. When the teacher got no response or got a wrong answer from the students, then the structure given was (s) h (post-h) (sel), the follow-up moves were mostly realized by (pre-h) h, the framing moves were realized by h q and the focusing moves were realized by h. Based on the analysis of the data, some conclusions can be presented as the following: (a) the types of moves found in the teacher talk were opening, follow-up, framing and focusing, while the answering moves were not found in the teacher talk, which indicates that the classroom is not effective because there is no initiation from the students, (b) the opening moves were mostly realized by h. When the teacher got no response or got a wrong answer from the students, then the structure given was (s) h (post-h) (sel), the follow-up moves were mostly realized by (pre-h) h, the framing moves were realized by h q and the focusing moves were realized by h. Therefore, to create an effective English classroom, teacher should be able to recognize the moves she applies in her talk.